The Russian world order before and after the Ukraine War - Hansen, Flemming Splidsboel (Politica, 2023)
For many years, the political debate in Russia has contained an element about a coming world order. There has been a general agreement that the state of affairs following the end of the Cold War was untenable, and that something different and more durable would replace the alleged US-led order. This debate has become more acute following Russia’s invasion of Ukraine on 24 February 2022. In the aftermath of the invasion, Russian president Vladimir Putin has reached out to the Global South in particular, and he has spoken about a more democratic, inclusive, and respectful order on numerous occasions. It is difficult to assess, however, to which extent his promises are caused by a need to forge new alliances, and to which extent Moscow is actually willing to reform for instance the UN system and allow the states in the Global South more influence.